Pengaruh Media Sosial dan Mesin Pencari Terhadap Peningkatan Penjualan UMKM - Gunawan, Deni (Eklektik : Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
This study aims to identify and evaluate elements of search engine optimization and social media activity that influence online purchasing decisions. In addition, the second objective of the study was to analyze the factors from internet advertising, social media, and search engine optimization that influence online purchase decisions. The method used in this study is descriptive and quantitative, with a qualitative literature survey approach to analyze data obtained from previous articles and journals. The results showed that search engine optimization and social media activity separately had a significant impact on increasing sales, while the combination of the two also had a significant impact on increasing sales